Mound 28 from the Paulje necropolis in Brezjak. A contribution to the absolute chronology of the Late Bronze Age in Serbia - Filipović Vojislav; Bulatović Aleksandar; Gligorić Rada (Starinar, 2022)
The paper brings the results of archaeological excavations of Mound 28 at the Paulje necropolis, conducted in the autumn of 2019, along with the excavations of two adjacent mounds. All of the aforementioned mounds were partially damaged and eroded through decades of ploughing. Consequently, remains of a Late Bronze Age burial were recorded solely in Mound 28. According to the grave inventory comprised of bronze jewellery and analogies from concurrent necropolises, it is assumed that the burial belongs to a female individual (?). Besides the extraordinary examples of bronze jewellery, such as pins, an arm ring, bracelets, crescent-shaped pendants, torques, and remains of amber jewellery, the organic substructure below the fully cast arm ring has been successfully dated. According to the absolute dating, the jewellery is attributed to the 14th century BC, and the inventory of the grave completely corresponds to the previously dated features from the Paulje necropolis. Therefore, certain forms of bronze jewellery were provided with a more precise chronological position based on the absolute dates. The burial is attributed to the Brezjak culture.